THE ROLE AND PRIORITY TASKS OF INDUSTRIAL ZONES IN THE ECONOMIC INDICATORS OF KASHQADARYA REGION - Xidirov Xurshid Jamshid o‘g‘li (American Journals, 2025)
This article discusses the role of industrial zones in the economic indicators of the Kashqadarya region and the priority tasks being implemented. It highlights how the region's location, rich natural resources both underground and above ground, contribute to industrial development. The article also examines the progress in industrial growth and provides recommended economic and scientific strategies necessary for further advancements.
Keywords: Unified Directorate of Small Industrial Zones,” special small industrial zones, “Entrepreneurship Infrastructure Development Fund,” auction sales.